Spatial and temporal distribution of culicoides insignis and culicoides paraensis in the subtropical mountain forest of Tucumn, Northwestern Argentina - Veggiani Aybar, Cecilia Adriana (2011)
Culicoides insignis Lutz and Culicoides paraensis Goeldi are known bluetongue virus and filariasis (caused by Mansonella ozzardi Manson) vectors, respectively. Bluetongue virus appears to be restricted to northeastern Argentina, while filariasis is endemic in the subtropical mountain forest of the Argentine northwest. With the objective of characterizing the abundance and seasonality of both Culicoides species, entomological sampling was carried out from Dec 2004 to Nov 2005 in the southern area of the forest of Tucumn province. The specimens were captured using CO2-baited CDC light traps placed in 2 types of environments, wild and anthropized. The abundance of the specimens in relation to environmental variables was analyzed using multiple linear regression. Out of the 2,497 adult specimens collected, 76.9% belonged to C. paraensis, 20.4% to C. insignis and the 2.5% belonged jointly to Culicoides debilipalpis Lutz, Culicoides lahillei Lutz and Culicoides venezuelensis Mirsa & Ortiz (2.5%), and 0.2% could not be identified. Peaks of abundance of C. insignis and C. paraensis in decreasing magnitude were observed in the fall, summer and spring, respectively; and the largest number of specimens was found in the anthropized environment. Mean minimum and maximum temperatures and levels of accumulated rainfall were the variables that best explained the abundance of these 2 species. The present work is an important contribution not only to the knowledge of the spatial and temporal distribution and dynamics of these vectors in nature, but also to the elucidation of the implications of anthropization of the forest environment, and the effect of these climatic variables as determinants of the abundance of the species and, hence, as determinants of the possible transmission of filariasis in the subtropical mountain forest of the Argentine northwest.